Developing a framework to strengthen the agility of South African manufacturing small and medium enterprises using best practices from Brazil, Russia, India, China and South Africa (BRICS) countries - Gcume, Nokonwaba Andiswa (Rhodes University, 2026)
The COVID-19 pandemic exposed significant vulnerabilities across global economies, prompting governments to re-evaluate the sectors essential for long-term economic stability and resilience. Although the pandemic had officially ended, its economic aftershocks continued to impede recovery, particularly in countries with pre-existing structural weaknesses. In South Africa, the manufacturing sector’s prolonged decline further highlighted the importance of organisational agility (OA) as a strategic capability that enabled firms to anticipate, adapt to, and respond effectively to emerging disruptions. However, most existing OA frameworks were generic, operationally focused, and insufficiently tailored to the specific needs of manufacturing SMEs, thereby limiting their ability to leverage agility as a source of competitive advantage. Drawing on best practices from BRICS country datasets, this study identified cross-learning opportunities that strengthened OA adoption and repositioned agility as a central driver of resilience within manufacturing SMEs. The literature showed that the absence of sector-specific OA frameworks constrained firms’ responsiveness to economic fluctuations and undermined their sustainability. Accordingly, the study examined the relationships between OA enablers and capabilities, organisational practices and processes, and the sense–response mechanisms that underpinned agile behaviour. While competitive advantage had traditionally been conceptualised through the Resource-Based View (RBV), which emphasised valuable, rare, inimitable, and non-substitutable (VRIN) resources, this study extended the theory by framing agility itself as a strategic resource that enhanced firms’ capacity for renewal in turbulent environments. Existing policies treated OA as standard procedure but did not include systematic monitoring. To address this gap, the study proposed a sector-specific OA framework for manufacturing SMEs, informed by BRICS best practices, to strengthen resilience and long-term competitiveness.
Keywords: Organizational resilience (http://id.loc.gov/authorities/subjects/sh2013000089); Manufacturing industries (http://id.loc.gov/authorities/subjects/sh97001369); Organizational effectiveness (http://id.loc.gov/authorities/subjects/sh85095526); Management; Competitiveness (https://www.wikidata.org/wiki/Q155953); Small and medium enterprises (https://www.wikidata.org/wiki/Q622439); Sustainable growth rate (https://www.wikidata.org/wiki/Q6134482)